Analisis Simulasi Antrian Teller Untuk Meminimasi Waktu Tunggu (Studi Kasus: BCA KCP Ruko Rajawali Palembang) - Dewi Purnama; Achmad Alfian (SAINTEK : Jurnal Ilmiah Sains dan Teknologi Industri, 2018)
Gueue is an important part of operation management. Queue takes place in the manufacturing and service sector. Queue is people or goods in a row waiting to be served and then leaving the row after being served. This study presents the results of modeling with simulation for analyzing the queuing system to minimize waiting time at teller of BCA KCP Ruko Rajawali Palembang. To reach the intended target steps taken is well planned research, describes the system in more detail to learn, build conceptual models and simulation models, simulate the model established, analyze and summarize output. Waiting time diverse 2 seconds to 1 hour and an average of 16 minutes 28 seconds and queue length of 1 to 20 people. These results show a good performance because the teller is not a long wait time. Capacity teller would be more effective if the teller in order to add a wait time faster than before. With the proposed queuing system, so the 5 tellers of the previous 4 tellers, has an average wait time to 12 minutes 36 seconds.